2022
DOI: 10.1038/s41467-022-30255-1
|View full text |Cite
|
Sign up to set email alerts
|

Ring walking as a regioselectivity control element in Pd-catalyzed C-N cross-coupling

Abstract: Ring walking is an important mechanistic phenomenon leveraged in many catalytic C-C bond forming reactions. However, ring walking has been scarcely studied under Buchwald-Hartwig amination conditions despite the importance of such transformations. An in-depth mechanistic study of the Buchwald-Hartwig amination is presented focussing on ligand effects on ring walking behavior. The ability of palladium catalysts to promote or inhibit ring walking is strongly influenced by the chelating nature of the ligand. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…For example, Larosa et al found that IPent enables efficient “exhaustive arylation” of various dihalogenated arenes despite a deficit of nucleophile . Further, Hein et al have reported that both IPr and RuPhos are effective di- or polyamination catalysts for regioselective elaborations of tetrabromospirobifluorenes . When a monofunctionalized product is desired, competitive overarylation detracts from the yield, in part because diarylated products can be challenging to separate from monofunctionalized product.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Larosa et al found that IPent enables efficient “exhaustive arylation” of various dihalogenated arenes despite a deficit of nucleophile . Further, Hein et al have reported that both IPr and RuPhos are effective di- or polyamination catalysts for regioselective elaborations of tetrabromospirobifluorenes . When a monofunctionalized product is desired, competitive overarylation detracts from the yield, in part because diarylated products can be challenging to separate from monofunctionalized product.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization is consistent with that in the literature. 20 1 H NMR (400 MHz, THF): δ 7.58–7.46 (m, 3H), 7.39 (dd, J = 8.1, 1.8 Hz, 1H), 7.04 (dd, J = 9.2, 2.1 Hz, 5H), 6.88–6.80 (m, 5H), 3.76 (s, 6H), 1.36 (s, 6H). 13 C{ 1 H} NMR (101 MHz, THF): δ 157.2, 156.6, 155.6, 150.1, 142.1, 139.6, 131.7, 130.8, 127.3, 126.8, 121.5, 121.29, 120.9, 120.2, 115.7, 115.5, 55.6, 47.8, 27.2.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization is consistent with that in the literature. 20 1 H NMR (400 MHz, THF): δ 7.39 (d, J = 8.3 Hz, 3H), 7.03 (d, J = 9.0 Hz, 8H), 6.82 (d, J = 9.0 Hz, 8H), 3.74 (s, 16H), 1.28 (s, 6H). 13 C{ 1 H} NMR (101 MHz, THF): δ 156.9, 155.5, 148.5, 142.5, 133.5, 126.9, 121.3, 120.3, 116.5, 115.4, 55.6, 47.3, 27.5.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations